Cyst of the jaws in artemisa maxillofacial department (2014)
Cysts are one of the most common causes of bone destruction of the Jaws. Cuba population has poor information about this topic; in our research we showed the range of the cyst of the jaws in maxillofacial department in Artemisa City, also we comparedwith others reports about the relation between sex and histological results. We founded 172 cyst 87 (50.6% in females and 85 (49.4%) in males. There were 9 types of cyst recognized by the WHO: the most frequently diagnosed were: radicular (periapical)  cyst (104 cases), residual cyst (24 cases), and dentigerous cyst (19 cases) with 85.4% of the all types of cyst. Mandibular cysts were more frequents. When we know the origin of the cyst, the clinical and histological behaviour of these types of diseases are very important in their medical and surgical management.